WORK MOTIVATION BASED ON ISLAMIC PRESPECTIVE - Rizky Wahyu Febrianto; Muzakki Muzakki (Ulumuna: Jurnal Studi Keilsman, 2021)
The purpose of this article is to know and understand more about the basic concepts of motivation in general and in particular in the Islamic perspective. Motivation is one of the important keys in achieving every goal of the organization, and motivation must be owned by every individual with the hope that the individual has the drive to work harder and has enthusiasm in achieving better performance, but on the one hand an individual does not forgets his identity that materialistic motivation and spiritual motivation are not independent of each other but are interdependent and interrelated which ultimately leads to good deeds that are blessed by Allah SWT to achieve happiness in this world and the hereafter.